Distillation of Essential Oils - Elise V. Pearlstine (EDIS)
Essential oils are volatile, aromatic oils obtained from plants and used for fragrance, flavoring, and health and beauty applications. Learn about the history of essential oils, plant anatomy, and basics of essential oil distillation in this 4-page fact sheet was written by Elise V. Pearlstine and published by the UF Department of Wildlife Ecology and Conservation, April 2011.